A Sociopragmatic Analysis On Commissive Utterances In Platoon Movie And Its Subtitle - Kurniasari, Riska (2012)
This research aims at describing the variations of language form, the equivalence and non equivalence intention,and describes the politeness strategies of commissive utterances used in Platoonmovie manuscripts and its subtitle. The type of this research is descriptive qualitative. The method of collecting data is documentation and observation method, and the steps are watching the original movies, reading the manuscript and its subtitle, underlying the commissive utterance, retyping the data, and coding the data of commissive utterance and its subtitle. To achieve the objectives the writer refersto linguistics form theory to identify the variation of language form in commissive utterances and its subtitling, Austin's theory of speech act to clarify the equivalence and non equivalence intention, and to describe the equivalence and non equivalence politeness strategies, the writer applies Brown and Levinson theory of politeness. The result of the study shows that the language form of commissive utterances in Platoonmovie manuscripts and its subtitle are 12,90% word is translated into word, 3,23% phrase is translated into phrase, 16,13% phrase is translated into word, 29,05% positive declarative sentence is translatedinto positive declarative sentence, 3,23% negative declarative sentence is translated into negative declarative sentence, 6,45% positive imperative sentence is translated into positive imperative sentence, 12,90% negative imperative sentence is translatedinto negative imperative sentence, 3,23% positive interrogative sentence istranslated into positive interrogative sentence, 6,45% positive exclamatory sentence is translated into positive exclamatory sentence, and 6,45% positive conditional sentence is translated into positive conditional sentence. The intention of commissive utterances in Platoon movie manuscript and its subtitle are 58,06% warning, 9,69% offering, 6,45% volunteering, 12,90% threatening, and 12,90% refusing. The politeness strategies are 41,93% bald on record, 25,81% positive politeness, 16,13% negative politeness, and 16,13% off record strategy.